2016
DOI: 10.4137/cmamd.s32269
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urinary Interleukin-6 in Assessment of Renal Activity in Egyptian Patients with Systemic Lupus Erythematosus

Abstract: AIM OF THE WORKThis study investigates whether serum and urinary interleukin-6 (IL-6) represent an early marker of kidney involvement and assesses the difference between them and renal biopsy in lupus nephritis (LN).PATIENTS AND METHODSA total of 60 systemic lupus erythematosus (SLE) patients were compared to 20 healthy controls. Urinary and serum IL-6 were measured in both patients and controls. In addition, renal biopsy was done prior or shortly after urine and blood sampling; the results were classified acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…However, an increase was not observed in cSLE patients compared controls. Our results corroborate the association of IL-6 with nephritis reported in some studies [ [30] , [31] , [32] , [33] ]. In addition, an anatomopathological study demonstrated increased IL-6 expression along glomeruli and tubules in the kidneys of patients with lupus nephritis, suggesting that IL-6 may be a biomarker for lupus nephritis [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, an increase was not observed in cSLE patients compared controls. Our results corroborate the association of IL-6 with nephritis reported in some studies [ [30] , [31] , [32] , [33] ]. In addition, an anatomopathological study demonstrated increased IL-6 expression along glomeruli and tubules in the kidneys of patients with lupus nephritis, suggesting that IL-6 may be a biomarker for lupus nephritis [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it will be more clinically helpful to evaluate the correlation between IL-6 and specific manifestations such as nephritis and central nervous system involvement. Although a few studies suggested that serum IL-6 might be associated with nephritis ( 56 ) and central nervous system involvement ( 57 ), it is hard to perform the relevant pooled analyses due to the lack of sufficient data in the included studies. Fourth, previous studies showed that corticosteroid therapy could effectively inhibit IL-6 production in SLE ( 58 , 59 ), suggesting that the difference in immune-suppressor therapy may overestimate or underestimate the correlation between IL-6 and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Organ-specific disease activity was determined by the presence of one or more positive scores in components of the SLEDAI-2K that pertain to different organ domains, as previously described ( 41 ). Renal SLEDAI-2K was defined using scores in the proteinuria, hematuria, pyuria, or urinary casts SLEDAI-2K descriptors ( 41 , 44 ). Persistently active disease was defined as SLEDAI-K score > 4 at both baseline and follow-up visit.…”
Section: Methodsmentioning
confidence: 99%